Statystyczne analizy zjawiska wykluczenia społecznego - problemy metodyczne i aplikacyjne - Borys, Tadeusz; Markowska, Małgorzata (Statistical Analysis of Social Exclusion - Methodical and Application Problems, 2007)
The study presents the concept of social exclusion as well as its core dimensions and the key problems of statistical analysis related to measuring such exclusion. In the article the general matrix scheme of indicator analysis was suggested and also the cause-result approach based respectively on the identification and measurement of factors determining the risk of social exclusion, the syndrome of such exclusion and its consequences, followed by the strategic reaction to social exclusion by means of measuring the extend of social integration objectives realization. There are also identified both strong and week points of cause-result approach in the statistical cause-result analysis. In the final part of the article Polish data records were assessed, related to the needs of social exclusion phenomenon indicator analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 82-89